2021
DOI: 10.1055/a-1661-4420
|View full text |Cite
|
Sign up to set email alerts
|

Thresholds of Basal- and Calcium-Stimulated Calcitonin for Diagnosis of Thyroid Malignancy

Abstract: Since medullary thyroid carcinoma is an aggressive cancer, it is important to have an early detection based on stimulated calcitonin (CT), especially when basal-CT is slightly elevated. The objective of this work was to set specific thresholds for basal-CT- and calcium-stimulated calcitonin for prediction of thyroid malignancy in female population. The study included 2 groups: group A-women with elevated basal-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…The Ct concentrations were determined with an immunochemiluminescence assay (ICMA) from Diagnostic Products Corporation (DPC, Los Angeles, CA), as described previously [3]. The ICMA results of this study were comparable with findings in other studies due to the worldwide use in many publications [14,15]. Blood samples for sCt determination during calcium-stimulated test (CST) were performed according to our previous publication described in detail [3].…”
Section: Bct Sct and Cea Levelssupporting
confidence: 74%
“…The Ct concentrations were determined with an immunochemiluminescence assay (ICMA) from Diagnostic Products Corporation (DPC, Los Angeles, CA), as described previously [3]. The ICMA results of this study were comparable with findings in other studies due to the worldwide use in many publications [14,15]. Blood samples for sCt determination during calcium-stimulated test (CST) were performed according to our previous publication described in detail [3].…”
Section: Bct Sct and Cea Levelssupporting
confidence: 74%
“…The application of serum Ctn levels has greatly helped in the diagnosis of MTC, especially in fine-needle aspiration (FNA) (19). Calcium stimulation (20,21) and pentagastrin (PG) (20,22) can be used to assist Ctn in differentiating C cell proliferation and MTC. Our previous study (23) (25) demonstrated that preoperative Ctn level, preoperative CEA level, and TNM stage were negatively correlated with biochemical cure.…”
Section: Discussionmentioning
confidence: 99%
“…Although other factors have been described as stimulating calcitonin secretion, pentagastrin (mainly) and the administration of venous calcium are true secretagogues, being important agents for the clinical evaluation of calcitonin secretion by normal and neoplastic cells (Wondisford, 2020;Wong, Nabata, & Wiseman, 2022). Some authors suggested that calcitonin is also responsible for the alteration of the postoperative calcium concentration in thyroidectomies (Băetu, Olariu, Nițu, et al, 2021;Băetu, Olariu, Stancu, et al, 2021;Tausanovic et al, 2021). Manipulation of the thyroid gland would lead to an increase in calcitonin secretion and, consequently, to a decline in calcium.…”
Section: Calcitoninmentioning
confidence: 99%